The General Equilibrium Model of Illegal Settlements in Palangkaraya City, Indonesia:-A Numerical Simulation- - Yuzuru Miyata; Indrawan Permana (European Regional Science Association (ERSA), 2012)
Since decade 80`s, colonies of illegal settlements began rapidly increasing in many urban areas of cities in Indonesia. During the decade, urban population living in slum areas was recorded about 54% of total urban population particularly in mega cities of Indonesia. Nonetheless, that percentage was increasing to be 69.12% in decade of 90fs. In line with that, in term of size, illegal settlement also increased to be 46.13% and 52.32% in decade 80`s and 90`s respectively (NUSSP, 2007). This urban phenomenon has been identified not only taking place in big cities but also taking place in small-medium cities with less than a million of population (Soegijoko et al ed, 2005). Aimed at to better understand the manner in which the illegal settlements come into being in Palangkaraya city, Indonesia, previously Permana and Miyata (2009) have developed a general equilibrium model of Palangkaraya city, Indonesia. Differing from Fujita`s model (Fujita, 1989), the model took into account land heterogeneity in a city thus rendering a typical land type of most cities in river basin areas. The model incorporated the expected flood damage rate (EFDR) on household assets. The EFDR itself is employed to predict the damage by the river flood since flood occurrences are stochastic and such appropriate flood data is not recorded well. Applying the general equilibrium modeling approach, one can derive the conclusion that the bid rents by low income households get higher than those by high income households in flood prone areas. This is the contrary conclusion being highlighted as compared with that in the traditional urban economics. This paper aims to show and discuss results of the numerical simulation of the model thus analyzing configuration of residential land use pattern in Palangkaraya city, Indonesia. The paper is organized as follows: Section 1 is for introduction. Section 2 is the general equilibrium model. Section 3 is the numerical simulation. And finally section 4 is aimed for conclusion.
Keywords: 330